In vitro antioxidant and antimicrobial activities of ethanolic extracts from whole plants of three Impatiens species (balsaminaceae) - Delgado Rodríguez, Fabián Vinicio (2018)
Context: Plants of Impatiens genus are recognized source of extracts with antioxidant and antimicrobial activity, including I. balsamina(Sanskrit name: Tairini), a plant traditionally used in Asia to treat infections and inflammation. However, there is little information related to activities of whole plant extracts. Aim: To investigate the in vitro antioxidant and antimicrobial activities of the ethanolic extract from whole plant of I. balsamina, I. hawkeri and I. walleriana. Methods: Whole plant material of each species was macerated with ethanol (80% v/v). Phytochemical screening was applied for detection of different metabolites. Total phenolic content (TPC) and total flavonoids content (TFC) were determined using Folin-Ciocalteu and aluminum chloride methods respectively. In vitro antioxidant properties were evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, potassium ferricyanide antioxidant reducing power (PFRAP) and oxygen radical absorbance capacity (ORAC) assays. In vitro antimicrobial activity of extracts was evaluated against Staphylococcus aureus(ATCC 29737), Staphylococcus epidermidis (ATCC 12228), Streptococcus pyogenes (ATCC 19615), Streptococcus pneumoniae (clinical isolate), Pseudomonas aeruginosa (ATCC 9027), Escherichia coli(ATCC 10536), Candida albicans (ATCC 10231) and Aspergillus niger (ATCC 16404) using microdilution assay for minimal inhibitory concentration (MIC) assessment. Statistical Analysis Used: Results were expressed as mean ± SD. Data obtained were analyzed statistically using ANOVA (one-way) followed by Tukey's post hoc test. Correlation analyses were performed using Pearson correlation test. Results: I. hawkeri extract showed the highest phenolic content (TPC: 44.04 mg GAE/g; TFC: 55, 02 mg QE/g) and was the most antioxidant extract. I. balsamina extract was the most active against all Gram positive bacteria (MIC: 2.5-10 mg/ml) tested and> over C. albicans (MIC: 10 mg/ml). This extract also showed the widest antimicrobial spectrum. Conclusions: The evaluated Impatiens whole plant extracts are also promising sources of antioxidant and antimicrobial agents.